Impact of Different NaCl Doses on Germination and Early Seedling Growth of Common Vetch Cultivars (Vicia Sativa L.) - Sibel Day; Satı Uzun (Turkish Journal of Agriculture: Food Science and Technology, 2016)
This study was conducted to investigate the NaCl impacts on germination and emergence performance of common vetch varieties. Seeds of Gülhan, Selçuk, Kubilay, Emir and Nitra were used as materials. Electrical conductivity (EC) values of NaCl solutions were 5, 10, 15 and 20 dS m-1. Distilled water (0 dS m-1) used as control. In this study germination and emergence test were applied to the varieties. In germination and emergence test mean germination time, mean emergence time, germination percentage, emergence percentage shoot length, root length, shoot fresh and dry weight were measured at the end of the 14th day after sowing. The results showed that germination and emergence percentage and the seedling growth of the varieties were inhibited by NaCl stress and NaCl stress led to increase in germination time and emergence time. Cultivars Gülhan and Emir were the least affected compared to other cultivars. Moreover increased NaCl levels gave rise to increase in Na+ content of cultivars and it was evaluated that the significant correlation (r=-0,525) between Na+ and K+. It was also determined that the correlation between two characters had negative relationship.